Randomized Double-Blind Study: Wound-Healing Effects of a Symphytum Herb Extract Cream (Symphytum×uplandicum Nyman) in Children - Barna, M.; Kucera, A.; Hladíkova, M.; Kucera, M. (Arzneimittelforschung, 2012)
The wound healing effects of the topically applied preparation Traumaplant® containing a concentrate (10% active ingredient) from the aerial parts of medicinal comfrey (Symphytum × uplandicum Nyman) were examined in a randomized, controlled, clinical double-blind study. An otherwise identical low-dose preparation (1% active ingredient) was used as a control. The study population consisted of 108 children aged 3–12 years (n=54/group) with fresh abrasions. A 50% healing rate was reached 0.9 days earlier with the higher than with the lower concentration cream. The difference in the healing rate (0.38±0.18/day [95% CI 0.33–0.4] vs. 0.26±0.14/day [95% CI 0.222–0.297]) was statistically significant (p=0.0002). Physicians and children/parents both rated the efficacy of the 10% cream as significantly better than that of the control preparation (physicians’ assessment after 2–3 and 7–9 days for verum vs. control: 90.7 and 92.6% vs. 55.6 and 74.0% of the healing rates were rated as ”good“ or “very good“, respectively; p=0.0004 and 0.01). In subgroup analyses, there was no significant influence on the healing rate of the time elapsed between the accident and the first consultation, the wound surface, the affected body part, the origin of the injury and gender. There were no reported adverse effects or problems with tolerability such as local skin irritations. The results justify application of the Symphytum herb extract cream in children with blunt traumata with or without abrasions.
Keywords: comfrey; Symphytum herb extract; topical application; wound healing; abrasions